Sliding Down the Slippery Slope? Trends in the Rules and Country Allocations of the Eurosystem's PSPP and PEPP - Annika Havlik; Friedrich Heinemann (Credit and Capital Markets – Kredit und Kapital, 2021)
This study analyzes trends in the Eurosystem's rules and country allocations of the Public Sector Purchase Program (PSPP) and the Pandemic Emergency Purchase Program (PEPP). The synopsis of purchase rules reveals how the ECB Council has loosened the initially strict constraints over time and various dimensions. For the year 2020, the analysis shows that the divergences of net purchases from the ECB capital key are substantive. The analysis of the PSPP stocks since 2015 illustrates that this increasing divergence from the capital key was on its way already before the pandemic. A final step of the analysis puts the PSPP/PEPP net purchases in proportion to current fiscal indicators. These results prove that, for several euro countries, the central bank net purchases fully match even the exceptionally high borrowing requirements of 2020. The study concludes with reflections on the challenges for a program exit after the end of the pandemic.
Keywords: H63; E42; H12; 330; quantitative easing; ECB capital key; fiscal dominance; unconventional monetary policy